Self-reported diabetes or hypertension diagnoses and antenatal care among child-bearing women in rural Bangladesh: A cross-sectional study. - Allyson P Bear; Wendy L Bennett; Joanne Katz; Kyu Han Lee; Atique Iqbal Chowdhury; Sanwarul Bari; Shams El Arifeen; Emily S Gurley (Public Library of Science (PLoS), 2023)
Health care systems in low- and middle-income countries may not meet the needs of pregnant women where the burden of diabetes and hypertension is rapidly increasing. We asked recently pregnant women about ever having been screened for or diagnosed with hypertension or diabetes and their ANC-seeking experiences in a cross-sectional survey. We used chi-squared tests and logistic regression to test the associations between self-reported coverage of hypertension and diabetes screening, diagnoses, and elements of ANC by age, wealth, educational attainment, and gravidity. Among 4,692 respondents, for hypertension, 97% reported having been screened and 10% of screened women reported a diagnosis. Women 30-39 years of age (aOR 3.02, 95% CI 2.00, 4.56) or in the top wealth quintile (aOR 1.70, 95% CI 1.18, 2.44) were more likely to be diagnosed with hypertension compared to reference groups. Any hypertension diagnosis was associated with reporting four or more antenatal care contacts (44% vs. 35%, p < 0.01), blood pressure measurements (85% vs. 79%, p < 0.01), and urine tests (71% vs. 61%, p < 0.01) conducted during ANC visits. For diabetes, 46% of respondents reported having been screened and 3% of screened women reported a diagnosis. Women 30-39 years of age were more likely to be diagnosed with diabetes (aOR 8.19, 95% CI 1.74, 38.48) compared to the reference group. Any diabetes diagnosis was associated with reporting four or more ANC contacts (48% vs. 36%, p = 0.04) and having blood testing during pregnancy (83% vs. 66%, p < 0.01). However, the frequency and quality of ANC was below the national guidelines among all groups. Focused efforts to ensure that women receive the recommended number of ANC contacts, coupled with improved compliance with ANC guidelines, would improve awareness of hypertension and diabetes among women in Bangladesh.